Pengaruh Kepemimpinan Transformasional dan Stres Kerja terhadap Motivasi Kerja dan Kinerja Karyawan - Siti Lailatul Ramadayanti (CV. Satria Jaya, 2023)
This study aims to examine the effect of transformational leadership and work stress on work motivation and employee performance. Transformational leadership in this study is proxied by idealized influence, intellectual stimulation, caring and motivation. Work stress is proxied by task demands, role demands, interpersonal demands and leadership. While Work Motivation proxies with the aim of employees working, employee behavior, employee enthusiasm and encouragement in employees. Employee performance is proxied by quantity, personal quality and timeliness. The sample of this research is PT. Indo Tirta Abadi Gempol Pasuruan. By using a saturated sample. Data obtained from distributing questionnaires. This study uses a variance-based Path Analysis method, namely WARP PLS. Based on the results of the study, it is stated that transformational leadership has a significant effect on motivation and work stress does not have a significant effect on work motivation. This study also states that Transformational Leadership has a significant effect on employee performance and job stress has a significant effect on employee performance. Meanwhile, work motivation on employee performance has no significant effect.